Soft ground improvement using pile embankment - Yahaya, Nor Ashikin (2019)
Construction on soft ground area is a great challenge to the field of Geotechnical Engineering. Soft ground area often affected by stability and settlement problems. The soft ground cannot take external load without having large deformations. Thus, soft soil improvement is needed. Soft ground improvement methods have been used in many parts of the world to minimize these problems. The problem could be minimized by many techniques such as Remove and Replace (R&R), Preloading technique with or without Prefabricated Vertical Drain and Pile Embankment. This study aimed to determine the suitable method to improve the soft ground in area of Lahad Datu, Sabah. This study conduct the interpretation of bore log obtains from the site investigations at the area of construction site need to be develop. From the bore log interpretation, the subsoil profile of this area consist of the very soft soils to soft soils which comprise a clayey soils and silty soils with varying thickness below the ground surface. The characteristic of soft soil is non-uniform and complicated which have high moisture content and loose sand deposit because this area is located near to the river. This research also analysed the primary consolidation settlement based on one-dimensional consolidation theory by Terzaghi (1984) due to the expected loading on site. This research has focus to eliminate the excessive settlement due to the heavy fill embankment and high bearing capacity. The settlement under 8.0m permanent fills about 473.4mm shows the settlement at this project area is a very excessive settlement. The Remove and Replace R&R method is not suitable to implement for this study because the soft soils layer is thicker which is about 15.0m of soft soils need to be removed and another 8.0 of embankment need to be filled to reach the finished level. The prefabricated vertical drain (PVD) method also not suitable as ground improvement method for this study area because PVDs are used to shorten the surcharging period and accelerate settlement not to reduce it. PVDs cannot load the high bearing capacity which is about 160 kN/m2 of loading need to support for embankment fill. Therefore, this study was decided to choose the pile embankment to load heavy fill embankment and to eliminate the effect of excessive settlement.